Mechanisms of the Effects of Zinc Oxide Nanostructures on Living Cells - Azam Javadi; maryam farzaneh; Saadati Mokhtar; Rohollah Azimirad; Fereshteh Esfandiari; Hamid Gourabi (Fasa University of Medical Sciences, 2020)
Nowadays, nanotechnology and nanostructures, which are particles smaller than 100 nm in size at least in one dimension, are being widely used in various industries and consumer products, biomedical applications and environments. Unique properties of Zinc oxide (ZnO) nanostructures offer technological advantages for a variety of industrial and consumer products as well as show promise for biomedical application. They are used as an antibacterial agent in food packaging, such as UV absorbent in cosmetics and sunscreens. However, high concentrations of ZnO nanostructures have toxic effects on living organisms. The toxic effect of these nanostructures depends on target cell type, size, structure, and surface properties of nanostructures, as well as exposure routes. In this article, we discuss the toxic effect of ZnO nanostructures and different mechanisms including ROS production and the resulting oxidative stress, genomic toxicity, changes in gene expression and following protein production, epigenetic changes and inflammatory responses and apoptosis. Also, we will mention many in vivo studies about this nanoparticle.